Determinan Kecemasan Ibu Hamil Selama Masa Pandemi Covid-19: Literatur Review - Whidy Lisarsa; Handayani Handayani (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2022)
Pregnancy is an exciting natural process because there will be an increase in the number of members in the family, but in reality not all mothers can go through the pregnancy process happily without any anxiety, especially during the COVID-19 pandemic. This study aims to determine the determinants of anxiety in pregnant women during the COVID-19 pandemic. This study used the Literature review method by filtering 2,120 journals into 5 articles obtained from google scholar. The results of this study indicate that the majority of pregnant women can experience anxiety both on a mild, moderate and severe scale, this is also influenced by the mother's level of knowledge and the mother's regularity in do a pregnancy check during the covid-19 pandemic.